Validação do instrumento de avaliação do jogador de futebol em situação de jogo - Kamimura, Márcio Kazuhiko [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
In the literature, it is possible to find a large number of studies directed toward athletic training in the physical, technical and tactical aspects of the Soccer game. In the other side, we are able to attest that there exists few instruments in the sport area of studies on evaluation of the athlete, in specific, rare are the instruments for assessment that takes into consideration the game situation. The most important aspect of an instrument of assessment is its validity. The present study has the objective to validate the “Instrument for Assessment of the Soccer Player” (IASP), proposed by Gama (2003). For the process of validation, participated nine university students, volunteers, four women and five men. The evaluators had a training period for acquaintance with the instrument and they analyzed, in individual basis, soccer games registered in video. This procedure was done via a 29 inches TV set, a DVD device and a voice recorder. Tests of reliability and objectivity were applied in order to measure intra and between observers consistency. As for the objectivity analysis, the results for each one of the soccer motor action with the ball in a game situation showed high correlation between possible score and obtained score. However these data did not allow for the validation of the IASP instrument as the criterion applied to the analyzed actions were different between observers even when of the observation of the same player in the same game. This problem was detected also in the evaluation of reliability. However, the present study was capable to point out inconsistencies within the Instrument for Assesment of the Soccer Player (IASP) so that after the needed changes being made, another validation will be done

Tem havido um grande interesse por parte dos pesquisadores no futebol pode ser detectado na literatura, com estudos focalizando o treinamento desportivo, nos aspectos físico, técnico e tático. Por outro lado, podemos afirmar que existem poucos instrumentos no campo esportivo para a avaliação do atleta e são ainda mais raros os instrumentos de avaliação que levam em consideração a situação de jogo. O mais importante de um instrumento de avaliação é a sua a validade. O presente estudo tem como objetivo a validação de um Instrumento de Avaliação do Jogador de Futebol (IAJF), proposto por Gama (2003). Para a validação desse instrumento participaram na validação nove universitários voluntários sendo cinco homens e quatro mulheres. Os avaliadores participaram de treinamento para a familiarização com o instrumento, e analisaram, de forma individual, jogos registrados em vídeo, através de uma TV de 29 polegadas, um aparelho de DVD e um gravador de voz. Foram realizados testes de objetividade e de fidedignidade a fim de verificar a consistência inter e intraavaliadores. Quanto aos testes de objetividade, os resultados para cada ação motora com bola durante o jogo mostraram uma alta correlação entre pontos possíveis e pontos obtidos, porém os dados não permitiram validar o IAJF, pois a aplicacao dos critérios para as ações analisadas foram diferentes entre avaliadores, mesmo quando da observação de um mesmo jogo e mesmo jogador. Este problema também foi detectado no teste de fidedignidade. Porém o presente estudo serviu para detectar inconsistências no Instrumento de Avaliação do Jogador de Futebol de modo que após feitas as alterações necessárias a validação será feita novamente
Keywords: Futebol; Futebol - Treinamento tecnico; Estudos de validação; Estudos de validação - Avaliação; Desempenho; Jogadores de futebol